PENGGUNAAN KOMUNIKASI FATIS DALAM PENGELOLAAN HUBUNGAN DI TEMPAT KERJA - Hendry Kurniawan; Aris Setiawan; Husni Mubarok (Yayasan Akrab Pekanbaru, 2020)
This study aims to identify the use of Verbal and Nonverbal Communication nature of phatic communication in building relationships and developing relationships in the workplace. This study also look at the context of the relationship Management Organizational Communication. This study was conducted to obtain a description of the role of verbal and nonverbal communication in the context of fascist communication and how to build interpersonal relationships that occur in the workplace. From the research, it was found that the use of fascist komunilasi very often occur in the workplace, because it is considered as an opener in a more intimate relationship. Phatic communication is important in making a relationship and create a close relationship between co-workers. Cultural context of someone very important role in the use of phatic communication, someone with a high-context culture tends to be more frequent use fascist communication communicates interpersonal relationships. But for those who are on a low cultural context also puts phatic communication to connect with colleagues in the interest of the work. The conclusion of this study, phatic communication is essential in building and managing relationships. This also applies in the workplace, phatic communication context is also related to the management of verbal and non-verbal language.